Registration quality and descriptive epidemiology of childhood brain tumours in Scotland 1975-90 (1994)
ABSTRACT: Children (0-14 years) with malignant brain and central nervous system (CNS) tumours (ICD9 191 and 192) were listed from the Scottish Cancer Registration Scheme for the years 1975-90. These cases formed the basis for validation and verification procedures aimed at providing a complete and accurate data set for epidemiological analyses. A variety of data sources were cross-checked to optimise ascertainment, and resulting from this 5.7% of validated cases were found on the cancer registry with diagnostic codes outside the ICD-9 range 191-192. A further 8.4% were newly registered cases. Analyses were conducted on the validated data set showing a significant temporal increase in incidence rates over the 16 year study period with an average annual percentage change of +2.6%. Large-scale geographical heterogeneity was also found, with a particularly high incidence in the Fife and Lothian areas and a low incidence in Grampian. Examination of associations with socioeconomic status, using the Carstairs deprivation index, revealed a rising trend in incidence strongly linked to areas with increasing levels of affluence. Our results suggest that for studies of childhood CNS tumours validation of cancer registry data is necessary and large-scale geographical variation and socioeconomic factors should be taken into account in any investigation of distribution in small geographical areas.